Web Based Tourism Information System in Bintan Island - Sherly Agustini (Engineering and Technology International Journal, 2022)
The use of the web or website as a medium to promote tourism places is increasingly being used. With the advancement of information technology as it is today, the development and promotion of tourism seems increasingly real. Minahasa Regency is blessed with extraordinary tourism potential, ranging from natural beauty, historical heritage, unique customs in Minahasa to various artistic and cultural attractions that are able to attract tourists both from abroad and within the country. With this Tourism Information System, it can provide a solution to increase the number of tourists visiting Minahasa. The method of implementing a web-based tourism information system in Minahasa Regency uses rapid application development that aims to meet user expectations in a relatively short time and produce a better system quality.